The Influence Of Work Attitude, Emotional Intelligence, Work Productivity And Work Motivation On The Effectiveness Of The Work Of Employees Of The Regional Revenue Agency Of Muara Enim Regency - Zahri, Ahmad; Aprini, Nisma; Ilpiyanto, Marko (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
This study aims to determine and analyze the effect of work attitude, emotional intelligence, work productivity and work motivation on the work effectiveness of employees of the Muara Enim Regional Revenue Agency. The research method used in this study is a quantitative method using questionnaires distributed to respondents. Test the quality of the data by using the validity test, reliability test, normality test. The analysis used is descriptive analysis and inferential analysis using statistical calculations with multiple regression formulas, partial tests and coefficient of determination. The results of the study showed that work attitude has a significant effect on the work effectiveness of employees of the Muara Enim Regency Regional Revenue Agency. Emotional intelligence has a significant effect on the effectiveness of the work of employees of the Muara Enim Regency Regional Revenue Agency. Work productivity has a significant effect on the work effectiveness of Muara Enim Regency Regional Revenue Agency employees. Work motivation has a significant effect on the work effectiveness of employees of the Muara Enim District Revenue Agency.